2021
DOI: 10.3390/app11199014
|View full text |Cite
|
Sign up to set email alerts
|

Traceable PM2.5 and PM10 Calibration of Low-Cost Sensors with Ambient-like Aerosols Generated in the Laboratory

Abstract: This work builds upon previous efforts at calibrating PM (particulate matter) monitors with ambient-like aerosols produced in the laboratory under well-controlled environmental conditions at the facility known as PALMA (Production of Ambient-like Model Aerosols). In this study, the sampling system of PALMA was equipped with commercial PM2.5 and PM10 impactors, designed according to the EN 12341:2014 standard, to select different aerosol size fractions for reference gravimetric measurements. Moreover, a metalli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…In the fourth paper, the focus is improving the effectiveness of low-cost sensors for air quality monitoring by advancing calibration methods. This study supports air quality control efforts and promotes more reliable and accurate monitoring and management practices [4]. The fifth paper presents the development of a multi-item air quality monitoring system that enables the real-time monitoring of various parameters.…”
Section: Advances In Gaseous and Particulate Air Pollutants Measurementmentioning
confidence: 55%
“…In the fourth paper, the focus is improving the effectiveness of low-cost sensors for air quality monitoring by advancing calibration methods. This study supports air quality control efforts and promotes more reliable and accurate monitoring and management practices [4]. The fifth paper presents the development of a multi-item air quality monitoring system that enables the real-time monitoring of various parameters.…”
Section: Advances In Gaseous and Particulate Air Pollutants Measurementmentioning
confidence: 55%
“…It is usually employed for atmospheric measurements. However, when used to characterize the size distribution in a flowing aerosol, it is common to connect a sampling tube to the inlet of the instrument [23,24].…”
Section: Optical Aerosol Spectrometer (Oas)mentioning
confidence: 99%
“…Their photometric measuring method operates via transmission effects, which results in a wider detectable particle-size range than with the SMPS. There are already a number of studies with the mentioned low-cost sensors [39][40][41][42][43][44], where the comparison to different laboratory measuring devices (Optical Particle Counter, SMPS, etc.) showed that the PM2.5 values are comparable [39,41,43].…”
Section: Measurement Devicesmentioning
confidence: 99%